1988
DOI: 10.1093/bja/61.5.617
|View full text |Cite
|
Sign up to set email alerts
|

Regional Skin Temperatures Associated With Total Sympathetic Blockade in Conscious Dogs

Abstract: Multiple regional skin temperatures were measured continuously before and after complete sympathetic nerve block by extradural anaesthesia in conscious dogs in environmental temperatures slightly below (22.4 (SEM 0.4) degrees C) and slightly above (27.2 (0.4) degrees C) the thermoneutral range. In the cold environment, skin temperature increased in the distal (+2.13 degrees C, P less than 0.001) and proximal (+1.1 degrees C, P less than 0.02) front limbs and distal (+3.25 degrees C, P less than 0.001) and prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…TEA was established with a bolus injection of mepivacaine 10 mg. kg-' (Carbocain" 20 mg.ml-l, Astra, Sweden), i.e. a similar dosage to that used previously during epidural anesthesia in dogs (18)(19)(20). Mepivacaine was then continuously infused epidurally at 5 m g ' k g -' .…”
Section: Measurement Protocolmentioning
confidence: 99%
“…TEA was established with a bolus injection of mepivacaine 10 mg. kg-' (Carbocain" 20 mg.ml-l, Astra, Sweden), i.e. a similar dosage to that used previously during epidural anesthesia in dogs (18)(19)(20). Mepivacaine was then continuously infused epidurally at 5 m g ' k g -' .…”
Section: Measurement Protocolmentioning
confidence: 99%
“…As previously discussed (16), caution must be exercised when relating changes in skin temperature directly to changes in sympathetic function. Recent observations by Arndt and coworkers may also partly explain these diverging findings (17). They showed that high epidural block in dogs was associated with increased skin temperature in both hind and front limbs while trunk skin temperature fell.…”
Section: Discussionmentioning
confidence: 97%
“…Sendo a bupivacaína o anestésico local mais utilizado, muitos relatos avaliam sua aplicação na anestesia peridural em cães enfocando bloqueios motor, sensitivo e autonômico (Feldman e Covino, 1988;Peters et al, 1988;Feldman et al, 1996;Feldman et al, 1997;Goméz de Segura et al, 2000). Nessas investigações têm sido testadas sua eficiência ou toxicidade de maneira isolada ou em combinação com outros fármacos (Timour et al, 1987;Peters et al, 1989;Hendrix et al, 1996;Goméz de Segura et al, 2000).…”
Section: Introductionunclassified
“…O bloqueio sensitivo também é avaliado pelo estímulo de introdução de uma agulha na pele dos cães e observação da contração dessa (Peters et al, 1988;Peters et al, 1989). Peters et al (1988) e Peters et al (1989) realizaram estudos relevantes a respeito da obtenção de bloqueio autonômico associado à temperatura cutânea em cães.…”
Section: Introductionunclassified
See 1 more Smart Citation